Needs Analysis and ESP Course Design: A Case Study of the Institute of Nutrition, Food and Agro-food Technologies - ELMECHTA, Lamia (Milev Journal of Research and Studies, 2022)
Needs analysis is the primary step for an effective ESP course design. The current work aims at analyzing the needs of Master 1 students for an ESP course from the perspectives of doctoral students and subject teachers at the institute of Nutrition, Food, and Agro-food Technologies (INATAA). To meet these targets, two questionnaires were administered, one for doctoral students and the other one for a sample of ten teachers at the institute of INATAA. The students’ questionnaire aimed to investigate thfrencheir current experience with the English language and the problems they encounter, their attitudes towards the past ESP course and their suggestions for ameliorating the course vis a vis their current needs. The teachers’ questionnaire was considered as a support to the students’ questionnaire for the amelioration of the course. The findings reveal that the major language problems encountered are text comprehension, technical vocabulary, writing and speaking skills. Despite these problems, the students show a positive attitude towards the target ESP course. Some suggestions have been offered by these students as well as subject teachers for the amelioration of the course.